LIDAR OUTGOING LASER ENERGY MEASUREMENT SYSTEM - Gibbons, Jasper (International Foundation for Telemetering, 2004)
International Telemetering Conference Proceedings / October 18-21, 2004 / Town & Country Resort, San Diego, California === A flexible system has been designed to accurately measure and average the outgoing laser energy of a micro-pulse LIDAR unit (MPL). This system incorporates specifically designed analog measurement circuitry interfaced with a microcontroller, allowing researchers to manage experiments from a personal computer. The final system produces a linearly proportional response between an incident laser energy input and the analog and digital circuitry’s output, accurate to within 0.1%. Custom designed algorithms allow the system to average the energy measured in a series of pulses. Each series can range on the order of tens of thousands of pulses.